2017
DOI: 10.1007/s13304-017-0450-z
|View full text |Cite
|
Sign up to set email alerts
|

Myoxinol ointment for the treatment of acute fissure

Abstract: Myoxinol is a complex of oligopeptides obtained from the seeds of Hibiscus esculentus used in cosmetic as natural alternative to botulin toxin. The aim of the study was to evaluate the safety and effectiveness of local myoxinol for the treatment of acute anal fissure. All the consecutive patients with acute fissure treated from January to June 2014 underwent 30 days of topical treatment (twice/day) with a mioxinol based ointment. Pain, symptomatic relief, fissure healing and re-epithelization, 1-year recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Alvandipour et al [ 20 ] reported that the mean VAS score level of the patients, who had received topical diltiazem treatment in the treatment of chronic anal fissure was 3.2± 0.25 at the beginning of the treatment, and the VAS score level was reduced to 2.32± 0.32 at the end of 1 month of treatment. On the other hand, in a study by Martellucci et al [ 21 ], evaluating patients with acute anal fissure, the median VAS score was 7.1 (range, 2–10) at the beginning of the treatment, and 1.7 at the end of 1 month of treatment. In a retrospective study of patients with acute anal fissure, Emile et al [ 22 ] reported that the mean VAS score level was 8.8 ± 0.96 before treatment, and the mean VAS score level was 0.47± 0.8 after 6 weeks of treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Alvandipour et al [ 20 ] reported that the mean VAS score level of the patients, who had received topical diltiazem treatment in the treatment of chronic anal fissure was 3.2± 0.25 at the beginning of the treatment, and the VAS score level was reduced to 2.32± 0.32 at the end of 1 month of treatment. On the other hand, in a study by Martellucci et al [ 21 ], evaluating patients with acute anal fissure, the median VAS score was 7.1 (range, 2–10) at the beginning of the treatment, and 1.7 at the end of 1 month of treatment. In a retrospective study of patients with acute anal fissure, Emile et al [ 22 ] reported that the mean VAS score level was 8.8 ± 0.96 before treatment, and the mean VAS score level was 0.47± 0.8 after 6 weeks of treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Then, we focused on other secondary endpoints: the proportion of patients healed at 1 week and then at 1-month follow-up and graded according to a previous published degree of reepithelisation scale (0—deep fissure still present, 1—superficial fissure, 2—partial reepithelisation, 3—complete healing and reepithelisation); by the end of fissurectomy, all patients were found to be at the lowest grade ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Parasympathomimetic medications such as Bethanechol and Indoramin (alpha blocker), beta agonists like Salbutamol, natural products like Myoxinol ointment [41], egg yolks [42], and injection of sclerosing agents [43] have been tried with varying results.…”
Section: Other Medications and Treatment Optionsmentioning
confidence: 99%